Bioaccumulation of Radionuclides and heavymetals by Pomacea canaficulata (Apple Snails) in Kampung Gajah district / Rifhan Mohamed Redwan - Mohamed Redwan, Rifhan (Faculty of Applied Sciences, 2008)
This study is an effort to initiate the information search on the containing of the radionuclide and heavy metals inside snails, Pomacea canaliculata form Kampung Gajah’s mines in Perak. The uptakes were taken from four different ex-mining lakes in Kampung Gajah. The samples were obtained every 3 months, first on August 2007, then on November 2007, the third obtained on February 2008 and the last one was on May 2008. The sampling area involved four lakes, from which sample collected, sample preparation from the separating the soft muscle from the shell. Then, the soft muscles, separated from the shells were sufficiently had to be dried to get the accurate result. The dried samples were grinded and sieved by the 212 micrometer sieve. Finally, the fine powders obtained which was of uniform size was then sealed in the vial and irradiated in the reactor TRIGA MARK II at 750 KW at Nuclear Malaysia by using the Nuclear Activation Analysis method. Two irradiation, short and long radiation were being used during the analysis. The elements identified from the short irradiations were V (3.448 ppm), Al (127367.496 ppm), Mn (174.526 ppm) and Cl (0.205ppm). These elements were from the first counting and the elements that have been obtained from the second counting were K(5919.684 ppm) and Na (2665.249 ppm). For long irradiation, the elements identified from the first count were adalah U (1.73303 ppm), Br (0.61626 ppm) and As (31.2323 ppm). The second count for long irradiation, the elements yielded were Yb (178.957 ppm), Th (2350.965 ppm), Cs (14.083 ppm), Sc (1.28143 ppm), Fe (2794.5 ppm) and Sm (228.846 ppm).